2002
DOI: 10.1063/1.1421630
|View full text |Cite
|
Sign up to set email alerts
|

Shock Hugoniot compression curve for water up to 1 GPa by using a compressed gas gun

Abstract: A shock Hugoniot compression curve for water has been measured up to less than 1 GPa. A plane and steady shock wave is produced in water by the flat plate impact of a projectile accelerated by a compressed gas gun. A new experimental procedure was proposed to detect the shock wave front sensitively, which makes it possible to measure shock Hugoniot in higher precision than the previous method. The present method is based on the very large pressure dependence of the refractive index of water upon compression. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 24 publications
(19 reference statements)
5
57
0
Order By: Relevance
“…We note that the shock Mach numbers are only slightly greater than 1 for the case of water alone (α 0 = 0) since the pressure perturbations (in water) up to several hundred atmospheres remain very weak (Thompson 1972). This fact was experimentally confirmed by Nagayama, Mori & Shimada (2002) and Inaba & Shepherd (2010).…”
Section: Quasi-one-dimensional Fsi Equationssupporting
confidence: 68%
“…We note that the shock Mach numbers are only slightly greater than 1 for the case of water alone (α 0 = 0) since the pressure perturbations (in water) up to several hundred atmospheres remain very weak (Thompson 1972). This fact was experimentally confirmed by Nagayama, Mori & Shimada (2002) and Inaba & Shepherd (2010).…”
Section: Quasi-one-dimensional Fsi Equationssupporting
confidence: 68%
“…The simulations utilizing the MG-EOS for liquid water do not match experimental data as well as the ideal gas simulations. Table 1 list the shock thickness and entropy generated for the two values of shock pressure investigated [5,10].…”
Section: Methodsmentioning
confidence: 99%
“…2; Table 1). We tested our simulation models against the plate impact studies of pure H2O by (Nagayama et al, 2002), using the target configurations and material parameters reported by these authors. Both results were in excellent agreement (with standard errors ≤ 5%) leading to a high level of confidence in our modelling procedures.…”
Section: Shewanella Oneidensis Mr-1 (Cip 106686) Was Purchased From Tmentioning
confidence: 99%